Tergerusnya Kesultanan Ternate: dari Pusat (Centre) ke Pinggiran (Periphery) Kekuasaan - Safrudin Amin (Universitas Khairun, 2015)
This article traces the change of political position of Ternate sultanate throughhistory from an independent traditional state in pre-European colonialismperiod, during its encounter with Europan colonialism from 16th centry to mid19th century, and in the period of being part of Indonesian nation-state todays.The author clearly argues that Ternate sultanate has undergonemarginalization process during the above-mentioned period from a centreand powerful independent state, which had many peripheral regionsgradually, becomes a powerless peripheral element of the present nationstateof Indonesia. The author also underlies some factors contributing to themarginalization process.